2011
DOI: 10.1242/dev.051888
|View full text |Cite
|
Sign up to set email alerts
|

FGF8 is essential for formation of the ductal system in the male reproductive tract

Abstract: SUMMARYDuring development of the urogenital tract, fibroblast growth factor 8 (Fgf8) is expressed in mesonephric tubules, but its role in this tissue remains undefined. An evaluation of previously generated T-Cre-mediated Fgf8-deficient mice (T-Cre; Fgf8 flox/D2,3 mice), which lack Fgf8 expression in the mesoderm, revealed that the cranial region of the Wolffian duct degenerated prematurely and the cranial mesonephric tubules were missing. As a result, the epididymis, vas deferens and efferent ductules were la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…5E–H). Fgf8 is expressed in and essential for the formation of cranial MTs (Kitagaki et al, 2011; Perantoni et al, 2005). Fgf8 was ectopically expressed throughout the IM in Shh KO embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5E–H). Fgf8 is expressed in and essential for the formation of cranial MTs (Kitagaki et al, 2011; Perantoni et al, 2005). Fgf8 was ectopically expressed throughout the IM in Shh KO embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Coiling and spatial arrangement of epididymal duct are governed by a complex signaling network involving testosterone signaling and a number of developmental signaling pathways (Cornwall, 2009; Di Giovanni et al, 2011; Hsia and Cornwall, 2004; Joseph et al, 2009; Kitagaki et al, 2011; Tomaszewski et al, 2007; Xu et al, 2010). Here we showed that Pkd1 is also an essential player in this regulatory network.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have surveyed the expression of growth factors in the epididymis and indicated the regional specific expression patterns for several growth factors [18,19]. A recent knockout study demonstrated that FGF8, which is expressed in the male reproductive tract, was essential for the formation of the ductal system in the epididymis, vas deferens, and efferent ducts [20]. Overexpression of FGF8b caused progressive stromal and epithelial changes in the epididymis in transgenic mice [21].…”
Section: Regulation Of the Basal Activity Level Of The Components Of mentioning
confidence: 99%